The Use Of Scaffolding Talks By Experienced And Novice Teachers At Junior High School And Senior High School In Kerinci District - Dika Sulmadianti (Poltanesa, 2022)
Scaffolding talks is temporary help and guidance that is designed to provide the assistance necessary to enable learners to accomplish tasks and develop their speaking ability. This research was descriptive qualitative. This research explains each type of scaffolding talk used by experienced and novice teacher of junior high school and senior high school in Kerinci district, and how they used to scaffold each type. The data of the research were utterances of the teachers, the data obtained through audio recording. The type used in this research were Instructing, Questioning, inviting students’ participation, Modelling, Explaining, Clarifying, Giving Feedback, Reviewing, Encouraging, and Gaining attention. The finding was all teachers used scaffolding talk in teaching English. Scaffolding talks types mostly used by experienced teachers were questioning, meanwhile novice teacher were modelling. How experienced and novice teachers used scaffolding in the classroom depends on context or situation and condition of the students.